2000
DOI: 10.1210/endo.141.2.7379
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Insulin-Like Factor 3 (Insl3) in Diethylstilbestrol-Induced Cryptorchidism

Abstract: Recently, it has been shown that targeted inactivation of the Insl3 gene in male mice results in cryptorchidism. The Insl3 gene encodes insulin-like factor 3 (Insl3), which is expressed in fetal Leydig cells. The testicular factor Insl3 appears to play an important role in the transabdominal phase of testis descent, which involves development of the gubernaculum. Other studies have demonstrated that in utero exposure to diethylstilbestrol (DES), a synthetic estrogen, can lead to cryptorchidism both in humans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(25 citation statements)
references
References 0 publications
2
22
0
1
Order By: Relevance
“…Insl3 is responsible for the transabdominal phase of testicular descent during first trimester through virilisation and outgrowth of the embryonic gubernaculum (Nef and Parada, 1999). Exposure to maternal oestrogens, including 17a-and b-estradiol, as well as diethylstilbestrol, downregulates Insl3 expression in embryonic Leydig cells (Emmen et al, 2000;Nef et al, 2000). On the other hand, based on the finding that oestrogens negatively regulate Leydig cell development via inhibition of replication of Leydig-cell precursor cells in adult and prepubertal rats, it is suggested that this regulatory mechanism may also control the number of Leydig cells in fetal life in humans (Sharpe and Skakkebaek, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Insl3 is responsible for the transabdominal phase of testicular descent during first trimester through virilisation and outgrowth of the embryonic gubernaculum (Nef and Parada, 1999). Exposure to maternal oestrogens, including 17a-and b-estradiol, as well as diethylstilbestrol, downregulates Insl3 expression in embryonic Leydig cells (Emmen et al, 2000;Nef et al, 2000). On the other hand, based on the finding that oestrogens negatively regulate Leydig cell development via inhibition of replication of Leydig-cell precursor cells in adult and prepubertal rats, it is suggested that this regulatory mechanism may also control the number of Leydig cells in fetal life in humans (Sharpe and Skakkebaek, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence shows that murine INSL3 expression is substantially reduced by diethylstilbestrol (DES), a drug associated with a higher incidence of cryptorchidism and other genital anomalies following human intra-uterine exposure (25,26). It will be interesting to determine whether this is part of the mechanism of action, of other environmental endocrine disruptors.…”
Section: Discussionmentioning
confidence: 99%
“…ERα has been shown to be a major contributor to estrogen-mediated cryptorchidism in ERα knockout mice [20]. Deleterious effects of estrogens and environmental estrogenic substances on CO have been also reported [21][22][23][24][25], and these previous findings highlight the importance of ESR1 in this scenario.Association of SNPs in canine ESR1 with CO has yet to be reported. In the present study, we analyzed SNPs and estimated haplotypes at the 3' end of the ESR1 in normal dogs and in different phenotypes of cryptorchid dogs (Miniature Dachshunds and Chihuahuas) to examine the presence of any associations of CO with the SNPs and haplotypes in the canine ESR1.…”
mentioning
confidence: 86%